Developing Task-Based Learning Materials to Improve Students’ Vocabulary Mastery Viewed from Linguistic Awareness - Noviana Naqsyabandiyah; Najmeh Dehghanitafti (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2023)
Task-based language learning is an approach that highlights the use of meaningful and authentic tasks in language learning activities. In practical terms, students engage in activities or language tasks that are designed to simulate real-life situations, where they must use the language to complete the task. This approach demands that teachers design learning materials in accordance with task-based learning frameworks. Among the linguistic aspects that have been considered as having a dominant effect on language teaching is linguistic awareness. Therefore, the present study aims to develop task-based learning materials for teaching vocabulary in EFL classrooms for 11th-grade students in secondary high schools, viewed from the perspective of students’ linguistic awareness. This study employs the 4Ds (Define, Design, Develop, and Disseminate) study method. The data collection comprises two types of data, namely qualitative and quantitative data. The quantitative data are analyzed using statistical methods, while the qualitative data are analyzed using techniques such as data condensation, data display, and drawing conclusions. The outcome of this study is an English vocabulary learning material based on task-based language learning activities for high school students in Central Lombok. The task-based learning material is designed based on the syllabus, student needs, school conditions, and level of ability that the researchers have previously analyzed, ensuring that the resulting product is in line with the students' and English teachers' needs.